The Influence of Work Motivation, Compensation, and Work Environment on Employee Performance at PT Prasetia Dwidharma Jakarta - Varsha P. K, Canthika Aulia; Pambreni, Yuni; Rachmawati, Dwi (Lead Journal of Economy and Administration, 2024)
This research aims to investigate the influence of work motivation, compensation, and work environment on employee performance at PT Prasetia Dwidharma Jakarta. The research method employed is quantitative, involving the distribution of questionnaires to 90 respondents from various divisions within the company. The collected data were analyzed using multiple linear regression with SPSS version 26. The results indicate that work motivation, compensation, and the work environment partially have a positive and significant impact on employee performance. Collectively, these three variables simultaneously have a significant influence on employee performance, with an adjusted R square value of 26.1%. Suggestions from the study are the company can pay attention to the individual needs of employees, enhance workplace safety, and continually monitor and improve these factors to achieve better work performance in the future.